The Effect of Phytoestrogen on Thyroid in Subclinical Hypothyroidism: Randomized, Double Blind, Crossover Study - Sathyapalan, Thozhukat; Dawson, Alison J.; Rigby, Alan S.; Thatcher, Natalie J.; Kilpatrick, Eric S.; Atkin, Stephen L. (Frontiers in Endocrinology, 2018)
Objective: Soy phytoestrogens are suggested to impair thyroid function but the effects of pharmacological doses of soy phytoestrogens are unknown; therefore, this study was performed to determine the effect of high dose soy phytoestrogens (66 mg) on thyroid function in subclinical hypothyroidism. Design and Setting: Randomized, double-blind, crossover study. Participants: 44 patients with subclinical hypothyroidism. Intervention: Participants were randomly allocated to either 66 mg phytoestrogen with 30 g soy protein (active) or 0 mg phytoestrogen with 30 g soy protein (placebo) supplementation for eight weeks, washed out for eight weeks and then crossed over for another eight week period. Main Outcome Measures: The primary outcome was progression to overt hypothyroidism with the secondary outcome measures were changes in thyroid function tests. Results: Two patients in this trial progressed into overt hypothyroidism after high dose phytoestrogen supplementation. TSH, free thyroxine and triiodothyronine did not differ between groups. Conclusion: A pharmacological dose of 66mg of soy phytoestrogens did not increase the overt thyroid failure rate or alter thyroid function tests in patients with subclinical hypothyroidism.